Port Rail Connectivity and Agricultural Production : Evidence from a Large Sample of Farmers in Ethiopia - Iimi, Atsushi; Adamtei, Haileyesus; Markland, James; Tsehaye, Eyasu (World Bank, Washington, DC, 2017)
Agriculture remains an important economic sector in Africa, employing a large share of the labor force and earning foreign exchange. Among others, transport connectivity has long been a crucial constraint in Africa. In theory, railways have a particularly important role to play in shipping freight and passengers at low cost. However, most African railways were in virtual bankruptcy by the 1990s. Using a large sample of data comprised of more than 190,000 households over eight years in Ethiopia, the paper estimates the impacts of rail transport on agricultural production. Methodologically, the paper takes advantage of the historical event that a major rail line connecting the country to the regional hub, the Port of Djibouti, was abandoned in the 2000s. With spatially highly disaggregated fixed effects and instrumental variables incorporated, an agricultural production function is estimated. The elasticity with respect to port connectivity is estimated at 0.276. The use of fertilizer is also found to increase with transport cost reduction, supporting the fact that a large amount of fertilizer is imported to Ethiopia.